Automatic motorbike side stand / Muhammad Amir Roslan and Suhadiyana Hanapi - Roslan, Muhammad Amir; Hanapi, Suhadiyana (School of Mechanical Engineering, 2023)
In today's world, two-wheeler vehicles play a crucial role in our lives as a means of transportation. They provide convenient travel from one place to another. However, they can also be a cause of both minor and major accidents when riders forget to lift off the side stand. The side stand serves an important purpose when the vehicle is at rest. Therefore, it is crucial to prevent riders from encountering this issue, which occurs frequently. One solution is to implement an automatic side stand mechanism in vehicles. This mechanism lifts the side stand automatically when the vehicle is starting or coming to a stop. The concept behind the automatic side stand is simple, easy to understand, and practical for real-life applications. In countries like Malaysia, there is a significant number of accidents caused by riders forgetting to lift off the side stand. This issue has serious consequences, impacting many lives. By installing this mechanism, we can effectively prevent such accidents from occurring.